Hypoglycemia in CDG patients due to PMM2 mutations: Follow up on hyperinsulinemic patients. Issue 1 (25th November 2019) - Moravej, Hossein; Altassan, Ruqaiah; Jaeken, Jaak; Enns, Gregory M.; Ellaway, Carolyn; Balasubramaniam, Shanti; De Lonlay, Pascale; Coman, David; Mercimek‐Andrews, Saadet; Witters, Peter; Morava, Eva
Abstract: Background: Phosphomannomutase 2 deficiency (PMM2‐CDG) is the most common congenital disorder of glycosylation (CDG). Hypoglycemia has been reported in various CDG including PMM2‐CDG. The frequency and etiology of hypoglycemia in PMM2‐CDG are not well studied. Methods: We conducted a systematic review of the literature on genetically and/or biochemically confirmed PMM2‐CDG patients who developed hypoglycemia. Prospective follow‐up information on the patients who received diazoxide therapy was collected and evaluated. Results: A total of 165 peer‐reviewed articles reporting on 933 PMM2‐CDG patients were assessed. Hypoglycemia was specifically mentioned only in 23 of these patients (2.5%). Hyperinsulinism was identified in 10 patients (43% of all hypoglycemic patients). Among these 10 patients, seven were successfully treated with diazoxide. However, most patients remained on therapy longer than a year to stay free of hypoglycemia. Conclusion: Hypoglycemia is a rarely reported finding in patients with PMM2‐CDG. Diazoxide‐responsive hyperinsulinism was found to have a good prognosis on medication in our PMM2‐CDG patients with hypoglycemia. No genotype‐phenotype correlation was observed with respect to hyperinsulinism. A prospective study should be undertaken to explore the hypothesis that hypoglycemia is underdiagnosed in PMM2‐CDG and to evaluate whether hyperinsulinism is always associated with hypoglycemia.